Hva kan vi lære av TALIS 2018? Gode relasjoner som grunnlag for læring - Björnsson, Julius K. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
" What are the specific challenges that teachers and school leaders face, and how do they feel about their working conditions? These are among the themes of the international TALIS study. The authors of this book take a close look at the 2018 survey that was carried out in 48 countries, including all of the Nordic countries. Topics explored include skills development for school administrators, innovation in schools and its significance, and use of IT in schools and in teaching. The book also addresses collaboration between teachers, and it looks at newly educated teachers' motivation and job satisfaction. The TALIS 2018 results are also viewed in relation to other Norwegian research in this field and can therefore lead to useful discussions and observations about Norwegian schools and Norwegian teachers and school administrators. The objective is to contribute to increased awareness of how schools function - and how they can be improved. The book is meant to inform not only school employees, teachers and administrators, but also those responsible for shaping national educational policy and the schools of the future."